Transform Behaviors, Transform Results! Identifying and Using Behavioral Indicators to Drive Sustainable Change and Improvement. - Jones, Morgan L.; Butler, Drew; Plenert, Gerhard Johannes (Milton : Productivity Press, 2022)
When trying to embed changes or new mindsets and behaviors, organizations tend to focus on following a particular methodology rather than clearly defining the underlying behaviors that will deliver the sustainable behavioral change and align the thought processes that drive the behaviors--whether their intent is to continuously improve safety or overall risk management or achieve a sustainable growth and improvement trajectory. The key role of leadership teams is not to deliver results. It is to inspire and own the organizational culture that delivers the expected results. If culture is owned by HR, it is doomed to be another thing leaders have to do on top of their day job. Business leadership teams must oversee defining and managing organizational culture and have HR coach the capability of leaders to cast the right leadership shadow by role modeling the right behaviors, rewarding the right behaviors in their teams, and providing clarity on expectations around behaviors for all leaders and employees. The most challenging part of any performance-improvement implementation is the identification of key behavioral indicators (KBIs). The purpose of this book is to assist with that challenge and make behaviors easier to understand and identify. The book defines and describes the importance of focusing on the behaviors necessary for sustainable change rather than focusing on the tools and methodology behind change management. It discusses multiple lenses of change including Lean, Six Sigma, Agile, Risk, and Customer Experience and also addresses the weaknesses of complying solely with the methodology and tools. It proposes a behavioral framework to suit each particular lens. This book begins with reasons most continuous improvement programs fail to deliver the expected results. More importantly, it discusses embedding the newly described mindsets and capabilities into the business. The book concludes by providing leaders a roadmap and a coaching framework for how to align and embed their new behavioral framework at all levels, starting from the front-line worker up to the CEO. Essentially, this book leads the reader through the process of understanding the concept of defining behaviors and the difference between them and tools/methodology. It introduces KBIs for leaders to define and drive the desired behaviors at all levels. This will increase the probability of sustainability for the improvement initiative by focusing on and maturing the behaviors these initiatives are trying to drive.
Description based upon print version of record.
Keywords: BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Workplace Culture; Organizational behavior; Corporate culture